2020
DOI: 10.1152/jn.00367.2019
|View full text |Cite
|
Sign up to set email alerts
|

Changes in motoneuron excitability during voluntary muscle activity in humans with spinal cord injury

Abstract: The excitability of resting motoneurons increases following spinal cord injury (SCI). The extent to which motoneuron excitability changes during voluntary muscle activity in humans with SCI, however, remains poorly understood. To address this question, we measured F waves by using supramaximal electrical stimulation of the ulnar nerve at the wrist and cervicomedullary motor-evoked potentials (CMEPs) by using high-current electrical stimulation over the cervicomedullary junction in the first dorsal interosseous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 52 publications
(87 reference statements)
1
24
0
Order By: Relevance
“…We also observed higher F-wave amplitude and persistence in SCI participants than in AB participants. This suggests an increased state of spinal motor neuron excitability after SCI, as has been noted by others [41], especially in the context of lesions in the rostral cervical cord [42]-of the 13 participants with SCI in our study, 6 had SCI at C3, and 2 had SCI at C4. Conversely, we observed a non-significantly higher unpaired H-reflex amplitude in AB participants than in SCI participants, which was surprising given that H-reflexes are usually increased below the level of SCI.…”
Section: Discussionsupporting
confidence: 85%
“…We also observed higher F-wave amplitude and persistence in SCI participants than in AB participants. This suggests an increased state of spinal motor neuron excitability after SCI, as has been noted by others [41], especially in the context of lesions in the rostral cervical cord [42]-of the 13 participants with SCI in our study, 6 had SCI at C3, and 2 had SCI at C4. Conversely, we observed a non-significantly higher unpaired H-reflex amplitude in AB participants than in SCI participants, which was surprising given that H-reflexes are usually increased below the level of SCI.…”
Section: Discussionsupporting
confidence: 85%
“…Some aspects of the timing of the application of TESS relative to performing the motor task, however, might be important to consider. The responsiveness of the motoneuron pool during voluntary activity also decreases following SCI (Vastano and Perez, 2020), which might benefit from extra inputs recruited by TESS. Our results showing effects on muscles innervated by segments distal to the applied stimulation site suggest that TESS effects extend below targeted segments.…”
Section: Functional Significancementioning
confidence: 99%
“…The relationship between MN degeneration and NMJ denervation in ALS remains elusive, but recent advances have demonstrated that NMJ functionality could play a crucial role in ALS development [ 21 ]. The homeostatic balance of MNs is especially refined due to their ATP-dependent axonal transport rate, axon length [ 22 ], and excitability pattern [ 23 ], demanding high support of adjacent cell populations under physiological and pathological conditions. Non-neuronal cells of NMJ (i.e., terminal Schwann cells and kranocytes) supply this nutritional, metabolic, and trophic supply, playing a key role in commandeering MN function and health (discussed in the NMJ section).…”
Section: Motor Neuron Degeneration As Non-cell Autonomous Processmentioning
confidence: 99%